Inked expressions: bridging the generational divide in Singapore's tattoo art and culture - Low, Andrea (Nanyang Technological University, 2023)
Ever wondered why tattoos are still frowned upon by the older generation in Singapore? Although attitudes towards tattoos are changing among youths who see it as art, social conservatives continue to associate tattoos with negative connotations, largely due to the Confucian value of filial piety and the association of tattoos with crime and punishment. This project seeks to understand the perspectives of the older generation and educate them about the evolution of tattoos as a form of self-expression that is no longer associated with criminality, but rather as a reflection of modern society. By delving into the cultural heritage of tattooing, which traces its roots back to 5000 BC and encompasses beliefs of power and protection, ceremonial practices, and methods of identification, alongside personally experiencing the tattoo process guided by tattoo artists. The project aims to foster a deeper understanding and appreciation of tattoos as an art form, ultimately leading to greater acceptance of tattoos as a means of personal self-expression.